Culinary-Gastronomic Value Advantage in a Competitive Dynamic Market: A Service-Dominant Logic Perspective - Augusty Tae Ferdinand; Raras Sekar Kinasih; Amie Kusumawardhani; Idris Idris; Irene Rini Demi Pangestuti; Hersugondo Hersugondo (Journal of Economics, Business, and Accountancy Ventura, 2022)
Since there are inconsistent findings on the influence of entrepreneurial orientation on business performance, we aim to develop a conceptual model to explain how an entrepreneurial orientation has the potential to enhance business performance. We develop a concept of culinary-gastronomic value advantage as mediation for entrepreneurial orientation to improve business performance effectively. We examine the model by involving 241 owner-managers of micro and small-sized enterprises in the food industry, whose results were analyzed using SEM-AMOS software. This study’s results indicate that the culinary-gastronomic value advantage derived from the Service-Dominant Logic (SDL) theory is an acceptable solution as mediation for entrepreneurial orientation and performance. Another important finding is that the entrepreneurial orientation and culinary-gastronomic value advantages are highly dependent on the level of risk consciousness on the competitive pressures that occur in the market. This study brings several theoretical implications to service-dominant logic theory, particularly on value accentuation in the form of culinary-gastronomic value advantage for enhancing performance.